Pengaruh Literasi Keuangan, Financial Technology, dan Inklusi Keuangan Terhadap Kinerja Keuangan UMKM di Desa Celep - Lestari, Dewi Arum; Fahriani, Dian; Wicaksono, Achmad; Anwar, Chairil (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
MSMEs have a significant impact on the national economy, particularly in terms of job generation and welfare. As a result, given the growing number of MSMEs and their significant contribution to GDP, they must master services, administration, and financial services. The purpose of this study is to ascertain how the financial performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Celep Village is impacted by the interaction of literacy, technology, and financial inclusion. The Slovin algorithm was used to pick 90 responders from a pool of 584 MSME actors. Data was collected using questionnaires and analyzed using SPSS. The results show that the financial performance of MSMEs in Celep is positively impacted by the three factors that were partially and concurrently analysed. This study highlights the significance of financial services accessibility, fintech use, and financial literacy in enhancing MSME financial performance